Perfectionism and learning experiences in dance class as risk factors for eating disorders in dancers - Penniment, Kylie; Egan, Sarah (John Wiley & Sons, 2012)
There is strong evidence that perfectionism is a risk factor for eating disorders. Women who engage in dance training have been reported to be at risk for eating disorders, and it has been hypothesised that expectancies about thinness and restricting food intake are formed partly as a result of exposure to thinness related learning (TRL) experiences in this environment, which may increase their risk. To clarify the relative contribution of perfectionism and learning in accounting for eating disorder symptoms in this group, 142 female ballet dancers completed an online survey. Through structural equation modelling it was found that the association between perfectionism and eating disorder symptoms was partially mediated by learning about thinness and restriction. The results suggest that eating disorder symptoms in dancers are significantly influenced by the interaction of perfectionism and learning, and future research should investigate the efficacy of prevention programs to target these risk factors in female dancers. Copyright © 2011 John Wiley & Sons, Ltd and Eating Disorders Association.